Flash Floods: Forecasting, Monitoring and Mitigation Strategies (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the mechanisms, modeling and controlling techniques of flash flood disasters, mainly in mountainous areas. Flash floods are among the most severe natural disasters, and the current publication will not only inspire future research but also enrich the current practice of flash flood disaster prevention and mitigation. This collection focusses on the engaged efforts in mitigating flash flood disasters, deepening the understanding of the causes of disasters in existing cases, finding appropriate modeling approaches, and implementing mitigation strategies. The readers will find within this reprint significant contributions for improving prevention and developing mitigation strategies, as well as protecting the safety of exposed populations.